THE ROLE OF CREATIVE ECONOMY IN COMMUNITY ECONOMIC EMPOWERMENT IN PAKU VILLAGE, KAYUAGUNG SUB-DISTRICT, OKU DISTRICT : EMA MULYADI KEMPLANG CRACKER BUSINESS - Wulandari, Vegi; Suryati, Suryati; Fitri, Hartika Utami (Multifinance, 2024)
This research aims to understand the role of the creative economy in empowering the community economy in the Paku sub-district, Kayuagung sub-district, Ogan Komering Ilir district. This research uses the empowerment theory approach according to Gunawan Sumodiningrat in looking at the success of community empowerment in fulfilling their lives. This research is qualitative, research using descriptive methods. Data collection was carried out using observation, interview, and documentation techniques, utilizing primary and secondary data sources, using a population of 4 employees plus one business owner as informants for Ema Mulyadi's kemplang cracker business. The results of this research show the role of the creative economy in empowering the community's economy in the kemplang cracker business, that the creative economy plays a very important role in economic growth in the community, with the existence of this creative economy, the community can take advantage of skills, ideas, and creativity to get opportunities to improve the economy. Based on the results of research on the role of the creative economy in economic empowerment, the Ema Mulyadi kemplang cracker business in the Paku sub-district can provide a role in the presence of job vacancies that do not look at the age of employees, improving the economy. In this economic improvement, business owners also often provide necessities and extra money when there are celebrations for big holidays, reducing poor people from this kemplang cracker business which employs 15 employees can reduce poor people in the Paku sub-district.